Performance analysis of orthogonal signals with TASP/MRC diversity - Guangqiu LI; Siting WANG (Dianxin kexue)
In order to solve the design problem of predictive transmit antenna selection (TASP) / receive antenna maximum ratio combining (MRC) wireless communication system with the minimum mean square error (MMSE) channel prediction,exact and approximate closed-forms for the average symbol error rate (ASER) of M-ary ortho-gonal and biorthogonal signals with coherent detection and TASP/MRC over Rayleigh block fading channel were de-rived by using parabolic cylinder function,the approximate expression of Gaussian Q-function and moment generat-ing function (MGF) based analysis approach respectively.Numerical and simulation results show that the theoretical analysis of the ASERs of orthogonal and biorthogonal signals is exact and the approximate closed-form for the ASER of orthogonal signals is accurate.The above exact or/and approximate closed-forms of ASER of orthogonal and biortho-gonal signals with coherent detection and TASP/MRC can be used to determine the number of antennas of transmitter and receiver and the parameters of predictor quickly,instead of the time-consuming and inefficient computer simulation.